ECONOMIC DEVELOPMENT AND ENTREPRENEURSHIP: A Critical Review From A Socio-Cultural Perspective - I Putu Tirta Agung Setiawan (Department of Management, Faculty of Economics and Business, Brawijaya University, 2012)
The aim of this paper is to briefly explain and analyse the association between entrepreneurship and development theories. It will exploit Schumpeter’s idea on economic development, especially on entrepreneurship as the main engine of that development process. It will also describe the reality of entrepreneurship in developing countries and discuss issues on the development of entrepreneurship study found in Indonesia as a case study. At the end, the paper concluded that a cultural study that link western theories of development and entrepreneurship with the unique cultural realities that exist only in developing countries is important.